Implementasi bahan ajar keterampilan membaca kritis bermuatan pesan moral dalam Cerpen Helvy Tiana Rosa - Sariyah Astuti; Dian Puspita (ARKA INSTITUTE, 2022)
This study aims to explore the implementation of Teaching Materials for Critical Reading Skills with Moral Messages, based on the short story